DISRUPTIVE MARKETING INNOVATION AS A MODERATOR OF THE INFLUENCE OF MARKETING STRATEGY ON PURCHASING DECISIONS AT THE SALATIGA CASSAVA MSME CENTER - Sudarwati, Sudarwati; Istiatin, Istiatin; Pradhana, Eryko Wisnu (STIE Pelita Nusantara Semarang, 2025)
This study aims to identify the role of disruptive marketing innovation as a moderator of the influence of marketing mix strategy, green marketing and social media marketing on purchasing decisions. This study uses a quantitative approach, with data collection techniques through surveys of consumers of Salatiga Cassava SMEs. Model and hypothesis testing uses SEM (Partial Least Square) analysis using SmartPLS. Based on the results of the analysis and discussion carried out in the previous chapter, the conclusions that can be drawn are as Marketing mix strategy has a significant effect on purchasing decisions, and disruptive marketing innovation. Green marketing does not have a significant effect on purchasing decisions but has a significant effect on disruptive marketing innovation. Social media marketing does not have a significant effect on purchasing decisions but social has a significant effect on disruptive marketing innovation. Disruptive marketing innovation has a significant effect on purchasing decisions but does not moderate or weaken the direction of the relationship between marketing mix strategy and green marketing on purchasing decisions but Marketing innovation moderates or strengthens the direction of the relationship between social media marketing on purchasing decisions. Keywords: purchasing; disruptive innovation; marketing mix; green marketing; social media